Investigation of g-C3N4/ZnAl2O4 and ZnO/ZnAl2O4 nanocomposites: From synthesis to photocatalytic activity of pollutant dye model - Sumetha Suwanboon (2020)
© 2020 Elsevier Ltd and Techna Group S.r.l. The fabrication of nanocomposite photocatalytsts with excellent photocatalytic activity is an important step in the improved degradation of organic dyes. A series of nanocomposite photocatalysts was synthesized with g-C3N4 and ZnO loading contents of 10, 20 and 30%. The nanocomposites were characterized by X-ray diffraction (XRD), Raman spectroscopy, scanning electron microscopy (SEM), transmission electron microscopy (TEM), Brunauer-Emmett-Teller (BET) surface area analysis, X-ray photoelectron spectroscopy (XPS) and diffuse reflectance spectroscopy (DRS). The optical band gaps of g-C3N4, ZnO and ZnAl2O4 were about 2.79, 3.21 and 3.55 eV, respectively. Methylene blue (MB) was degraded over the prepared photocatalysts under UV irradiation. Photocatalytic activity was about 9.1 and 9.6 times higher, respectively, on 20%g-C3N4/ZnAl2O4 and 20%ZnO/ZnAl2O4 nanocomposite photocatalysts than on pure ZnAl2O4 spinel powders. Recycling experiments showed that 20%g-C3N4/ZnAl2O4 and 20%ZnO/ZnAl2O4 nanocomposite photocatalysts exhibited good stability after five cycles of use.